Impunity and the inner history of life - Rojas B., Paz (Social justice, 1999)
Part of a special issue on state terrorism and impunity in Latin America. The writer, drawing on a medical, psychological, and social practice, reflects on the victims of persecution, torture, executions, disappearances, and exile in Chile. He reports that these experiences began in 1973, in the wake of the military coup, and persisted for the following 17 years of state terrorism. He notes that the study later explored the consequences of the absence of truth and justice for individuals and for society as a whole. He explains that, appalled by the tortured bodies, physicians tried to systematize the kind of disorders found and outlined this phenomenon within the context of their clinical practice. He asserts that they used two approaches: the phenomenological-existential, which allows knowledge of the inner self of the persons treated and the conditions of their existence; and the multidisciplinary-systemic, which permits a global assessment of the trauma.